2021
DOI: 10.2478/aut-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Seersucker Woven Fabrics

Abstract: The surface characteristics of fabrics are important from the point of view of the sensorial comfort of clothing users. Surface friction and surface roughness are the most important surface parameters of fabrics. These parameters can be measured using different methods, the most important and well-accepted method being that using the Kawabata evaluation system (KES)-FB4 testing instrument. In this work, the surface roughness and surface friction of the seersucker woven fabric have been determined using the KES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These fabric structures indicate little frictional resistance to movement applied to their surface. Some studies assume that fabric's low friction coefficient is less affected by the mechanical effects resulting of low abrasion [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fabric structures indicate little frictional resistance to movement applied to their surface. Some studies assume that fabric's low friction coefficient is less affected by the mechanical effects resulting of low abrasion [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Tekstil ve Konfeksiyon 33 (1), 27-36. Friction properties of fabrics vary according to fiber content variations, yarn properties, fabric structure, and finishing processes [12]. In polyester blends made with cotton and viscose fibers, it was found that the friction force increased as the cellulose ratio increased in the blend [9]. Due to the variation of fabric surfaces, the friction resistance of fabrics is not always linearly proportional.…”
Section: Introductionmentioning
confidence: 99%
“…Matusiak's studies explore the structural, mechanical, and moisture transport properties of seersucker fabrics, as well as their comfort-related characteristics [1,12,17,18]. The research conducted by Matusiak and Bajzik focuses on surface characteristics and the effect of seersucker repetition on fabric parameters [14]. Furthermore, Matusiak utilizes noncontact optical methods to investigate the surface geometry of seersucker fabrics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Seersucker fabrics can achieve regional shrinkage eff ect by using various chemicals on the fabric. The shrinking eff ect is achieved by using chemicals such as caustic soda and sodium hydroxide in the desired areas, but the shrinking eff ect cannot be maintained in long-term use [13,14]. With the development of weaving technology, it has become possible to produce elastane-containing grades on single-beam looms, and this production method is now widely used [15].…”
Section: Introductionmentioning
confidence: 99%